2019
DOI: 10.3389/fvets.2019.00235
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Arctigenin and Fructus Arctii Powder in Piglets

Abstract: Fructus arctii, also known as great power seed, is the dried fruit of Arctium lappa of the family Compositae. It is a commonly used veterinary herbal medicine, and arctigenin is the main active ingredient. The aim of this study was to characterize the absorption, distribution, metabolism, and excretion of arctigenin and Fructus arctii powder in piglets. These data were used to provide a theoretical reference for the development and clinical use of new veterinary drugs. Sixteen healthy pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This suggested that the metabolic stability of ATG showed differences in the liver microsomes of different species. Respectively, another study using 2 mg/kg of ATG administered intravenously to piglets compared with gavage at a dose of 1000 mg/kg revealed that intravenous ATG had limited distribution in tissues, while oral ATG was more rapidly absorbed, more widely distributed, and more slowly eliminated to achieve longer‐lasting pharmacological effects (He et al, 2019). The results of in vitro microsomal culture experiments in rats by Gao et al (2014).…”
Section: Pharmacokinetics Of Lignansmentioning
confidence: 99%
“…This suggested that the metabolic stability of ATG showed differences in the liver microsomes of different species. Respectively, another study using 2 mg/kg of ATG administered intravenously to piglets compared with gavage at a dose of 1000 mg/kg revealed that intravenous ATG had limited distribution in tissues, while oral ATG was more rapidly absorbed, more widely distributed, and more slowly eliminated to achieve longer‐lasting pharmacological effects (He et al, 2019). The results of in vitro microsomal culture experiments in rats by Gao et al (2014).…”
Section: Pharmacokinetics Of Lignansmentioning
confidence: 99%
“…The injection volume was 10 µL. The column temperature was maintained at 30 • C, and the detection wavelength was 280 nm (Ju, 2008;He et al, 2019).…”
Section: Determination Of Arctiin and Arctigeninmentioning
confidence: 99%
“…The main active components are lignans, including arctiin and arctigenin. Arctiin has low bioavailability but can be converted into arctigenin by gastrointestinal microorganisms (Hu et al, 2004;Yu, 2007;He et al, 2019). Modern science has demonstrated that arctigenin is beneficial for the treatment of viruses (Swarup et al, 2008;Hayashi et al, 2010), tumours (Matsumoto et al, 2006;Kim et al, 2010), inflammation (Zhao et al, 2009), allergy (Lee and Kim, 2010), shock (Ishihara et al, 2006), bacteria (Liu, 2008), and parasites (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bulbus Fritillariae Cirrhosae and Rhizoma Bletillae are the main components of NBXH, which have the functions of heat clearing, lung moistening, phlegm resolving, cough relieving, hemostasis, and detumescence [ 8 10 ]. Herba Houttuyniae , Radix Platycodonis , and Fructus Arctii are the auxiliary elements of NBXH, which have the beneficial effects of acting as an anti-inflammatory, reducing phlegm, and relieving cough as well as sore throat [ 11 13 ]. Glutinous rice is used as the adjuvant to invigorate the spleen, stomach, and lung [ 14 ].…”
Section: Introductionmentioning
confidence: 99%